Netflix’s Glocalization Strategy in Framing Instagram Content in Indonesia and Australia - Nadiatul Aulia; Ayuning Arisanti Nugrahani; Airlangga Kautsar (Interdisciplinary Social Studies, 2026)
Everything has to adapt if it wants to survive. Social media is also the same. If observed, brands today make various efforts in building and conveying messages to customers across all cultures. This study examines how Netflix adapts its Instagram communication in Indonesia and Australia while maintaining a consistent global brand identity. Using a qualitative content analysis of Instagram posts from @NetflixID and @NetflixANZ promoting Bridgerton Season 4, this study applied Hofstede’s cultural dimensions and the concept of glocalization as analytical frameworks. The findings show that Netflix employed the same global visual promotional assets across both accounts but adapts message delivery through language choice and caption style. The Indonesian account uses a more narrative and expressive caption style, whereas the Australian account adopts a more concise and thematic approach. These differences indicate that glocalization is implemented at the level of communication rather than visual content and reflect Netflix’s adaptation to culturally shaped patterns of digital consumer behavior. This study highlights the importance of culturally responsive communication strategies in global brand communication on social media.